GINGIVAL CYST OF ADULTS- TWO CASE REPORTS AND LITERATURE REVIEW - Elitsa G. Deliverska; Aleksandar Stamatoski (Peytchinski Publishing, 2018)
Background: Gingival cyst of adult is an uncommon, small, non inflammatory, extra-osseous, developmental cyst of gingiva arising from the rests of dental lamina. Purpose: The aim of our paper is to present two rare clinical cases of gingival cyst of adult. Material and methods: In the present cases, the combined anatomic characteristics of the soft tissue presentation and the osseous defect suggest that the lesion is a gingival cyst of adult. Two cases of gingival cyst were diagnosed and treated with exicisional biopsy followed by histopathological confirmation and an emphasis on the clinical aspects of this lesion. Results: The biopsy revealed histologic features consistent with a gingival cyst. Clinical and radiographic examinations 1-year post-surgery indicated uneventful soft tissue healing and bone fill of the initial defect. Conclusion: Gingival cyst most commonly occurs on the labial side of the mandible in the canine and premolar areas. It is discrete, well-cirumscribed, painless swelling of the attached gingiva or gingival papilla. This is a soft tissue lesion, and if enlarged to sufficient size, it causes superficial erosion of the cortical plate of bone. Lesions appear to be asymptomatic and do not produce discomfort. It is a fairly rare cyst or at least it is rarely sent for biopsy.